Supercritical Fluid Extraction of Major Bioactive Flavonoids from Spearmint (Mentha Spicata L.) Leaves - Bimakr, Mandana (2009)

(untitled)
Supercritical fluid extraction (SFE) is an attractive alternative technique to conventional liquid extraction due to its several distinct properties. This novel interesting extraction method which was developed in 1960 is an energy efficient, economically viable and environmentally friendly process. This study evaluated the effect of supercritical carbon dioxide extraction on the extraction yields and major bioactive flavonoid compounds from the herbal matrices. Two basic extraction methods were investigated: conventional soxhlet extraction (CSE) and supercritical carbon dioxide (SC-CO2) extraction. High-Performance Liquid Chromatography (HPLC) was used to identify and quantify bioactive flavonoid compounds of produced extracts. Results obtained from the two extraction methods were compared for a higher extraction yield and concentration of flavonoid compounds. In the study of supercritical carbon dioxide extraction and conventional soxhlet extraction spearmint (Mentha spicata L.) leaves were selected. For optimizing of SC-CO2 extraction process three most important variables including temperature, pressure and extraction dynamic time have been studied. The full factorial in complete randomize design (CRD) based on three levels and three factors was employed to obtain the optimum condition for SFE. Based on the simultaneous optimization of crude extract yield and concentration of flavonoid compounds the optimum condition was found at temperature of 60 ᵒC, pressure of 200 bar and extraction dynamic time of 60 min. In conventional soxhlet extraction study, different solvents were used to evaluate the effect of different applied solvents on the extraction yield and major bioactive flavonoid compounds. Ethanol: water (70:30) was found as a preferable solvent among the other applied solvents due to its higher extraction yield, flavonoid compounds concentration and lower toxicity effects. Compared with supercritical carbon dioxide extraction the higher concentration of bioactive flavonoid compounds was obtained and extraction time was reduced by applying SC-CO2 extraction. However, the higher crude extract yields were obtained by using conventional soxhlet extraction. The influence of co-solvent (modifier) on the extraction yield and extracted flavonoid compounds from spearmint (Mentha spicata L.) leaves was also studied. In this study ethanol acted as co-solvent to improve the efficiency of polar compounds (flavonoids) extraction. Co-solvent flow rate of 6 g/min was found as a preferable modifier flow rate to obtain higher extraction yield and bioactive flavonoid compounds concentration.